Power Hegemony: The New Era of Chinese Socialism with the Character of XI Jinping - Arthuur Jeverson Maya (International Journal of Social Service and Research, 2023)
This research seeks to unravel the influence of Xi Jinping's "superpower" on the world as a sign of a new era of Chinese socialism with the character of Xi Jinping. Reliable and mystical ideas put Xi Jinping on an equal footing with Mao Zedong and Deng Xiaoping. This means that the dogma of Chinese socialism is entering a new era with the character of Xi Jinping's thought. Using the theory of hegemony proposed by Ernesto Laclau, this research reveals Xi Jinping's ideas that are the truth agreement of Chinese society and the regions within the framework of the Belt and Road Initiative. More than his predecessors, Xi Jinping has sought to lock down western ideas and push for economic harmonization of a version of "market socialism."